ANALISIS PENGARUH BERWUDHU TERHADAP PERUBAHAN TEKANAN DARAH SESAAT - Achmad Akbar Ramadhan; Mochammad Erwin Rachman (Fakultas Farmasi UMI, 2015)
The ablution is a very important Islamic teachings as a condition of validity of prayers, besides ablution provide a very important benefit to human health. Objective: To determine the effect of berwudhu to changes in blood pressure on high school students shortly Global Mandiri Al - Ashri Makassar. Methods: This study used a survey method that uses the analytic approach of Cross Sectional. The samples used were mostly high school students Global Mandiri Al - Ashri Makassar as many as 50 people. Results : The results showed a mean systolic blood pressure was 123.56 mmHg before her ablutions, then after berwudhu 122.28 mmHg. Mean diastolic blood pressure before berwudhu was 64.08 mmHg , and 62.32 mmHg after her ablutions, with kemanaknaan p > 0.005 ( p = 0.270 ). Conclusion : There is a change in blood pressure just before and after her ablutions, although it is not significant.